2022
DOI: 10.1371/journal.pgph.0000458
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress, stigma, and social support among Nepali health care workers during COVID-19 pandemic: A cross-sectional web-based survey

Abstract: The COVID-19 pandemic has caused immense psychological distress among Health Care Workers (HCWs). HCWs have been stigmatized by people at their workplace and community, fearing that health care workers are the sources of spreading the virus. This study aimed to assess the perceived stress, stigma, and social support of Nepali health care workers during the COVID-19 pandemic. A web-based cross-sectional survey was conducted among 380 Nepali HCWs. Perceived stress was measured using Perceived Stress Scale (PSS-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Stigma related to infectious diseases occurs frequently among HCWs. A systematic review showed that 28% of HCWs experienced stigma and 31% perceived stigma [22], which is comparable to studies reporting on COVID-19 HCWs (proportions ranging from 35%-57%) [23][24][25][26]. Participants from our study expressed that the stigma was mainly rooted in the fear of infection.…”
Section: Discussionsupporting
confidence: 77%
“…Stigma related to infectious diseases occurs frequently among HCWs. A systematic review showed that 28% of HCWs experienced stigma and 31% perceived stigma [22], which is comparable to studies reporting on COVID-19 HCWs (proportions ranging from 35%-57%) [23][24][25][26]. Participants from our study expressed that the stigma was mainly rooted in the fear of infection.…”
Section: Discussionsupporting
confidence: 77%
“…When compared to public health professionals, paramedics professionals had a 4.6-fold more favorable attitude toward the COVID-19 booster dose. The most likely explanation could be that paramedic health professionals worked in laboratories collecting samples of COVID-19 (nasopharyngeal swabs) and radiological departments and therefore at more risk of contracting COVID-19 due to close contact with the cases 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Our few study participants faced stigma from close friends or family members, such as when your family members are scared of you. Giri et al (2022) revealed that healthcare workers in Nepal experienced significant levels of perceived stress and stigma during the COVID-19 pandemic, while also highlighting the crucial role of social support in mitigating these negative effects (Giri et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Giri et al ( 2022 ) revealed that healthcare workers in Nepal experienced significant levels of perceived stress and stigma during the COVID-19 pandemic, while also highlighting the crucial role of social support in mitigating these negative effects (Giri et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%